Demands and Challenges of Publication of Scientific Writing for Arabic Language and Literature Students - Abidin, Zaenal; Nuur, Khaerun Nisa; Satrianingsih, Andi; Arifin, Nur (Jurusan Ilmu Perpustakaan dan Informasi Islam Universitas Islam Negerin Datokarama Palu, 2022)
This study aims to describe the competence of Arabic Language and Literature students at Faculty of Adab and Humanities of UIN Alauddin in producing scientific papers by testing the effectiveness of demands and confirming the challenges faced. The focus of the objects and data sources of this study were students majoring in Arabic in semesters 5 and 7 who were found randomly or random sampling. Presentation of data is done descriptively. Data analysis and drawing conclusions are done inductively. The results of the research show that Arabic Language and Literature (BSA) students are not aware of the opportunities they have to conduct research and produce scientific papers (KTI). This has implications for the increasing challenges they face, because in addition to their inability to utilize a number of supporting facilities, they also lack research and writing experience. In fact, because the inability to seize opportunities makes them less motivated and weak in interest. Abstrak Penelitian ini bertujuan untuk mendeskripsikan kompetensi mahasiswa Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Alauddin dalam menghasilkan karya tulis ilmiah dengan menguji efektivitas tuntutan dan mengkonfirmasi tantangan yang dihadapi. Fokus objek dan sumber data penelitian ini ialah mahasiswa jurusan Bahasa Arab semester 5 dan 7 yang ditemukan secara acak atau random sampling. Penyajian data dilakukan secara deskriptif. Analisis data dan penarikan kesimpulan dilakukan secara induktif. Hasil penelitian menunjukkan kurang sadarnya mahasiswa Bahasa dan Sastra Arab (BSA) terhadap peluang yang mereka miliki untuk melakukan penelitian dan menghasilkan karya tulis ilmiah (KTI). Hal itu berimplikasi terhadap bertambahnya tantangan yang mereka hadapi, sebab di samping ketidakmampuan memanfaatkan sejumlah fasilitas pendukung, juga minimnya pengalaman meneliti dan menulis. Bahkan karena ketidakmampuan menangkap peluang menjadikan mereka kurang motivasi dan lemah minat.